FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU HAMIL TRIMESTER III MENJELANG PERSALINAN DI BIDAN PRAKTEK MANDIRI BUNDA ABROR TAHUN 2022 - Nurul Mouliza; Ina Rahawa (Jurnal Maternitas Kebidanan, 2023)
Anxiety is an emotion, a feeling that arises as an initial response to psychological stress and a threat to values that are meaningful to the individual. Anxiety is often described as feeling uncertain, doubtful, helpless, restless, worried, uneasy accompanied by physical complaints. Based on an initial survey conducted for 8 trimester III maternal  amounted 6 have anxiety and 2 were not worried and had prepared themselves for childbirth. The purpose of this study was to determine what factors were associated with anxiety of third trimester maternal before delivery at the Midwife of Independent Bunda Abror in 2022. The design in this study used an analytic survey with cross sectional approach. The population in this study were all trimester III maternal in the Bunda Abror Maternity Clinic amounted 30 respondents. The sampling technique uses total population. Data collection using a questionnaire. Univariate and bivariate data analysis with chi-square test at 95% confidence level. The results of the study with the chi-square test found p values between knowledge with anxiety p=.006, age with anxiety p value=.010, parity with anxiety p =.046 and education level with anxiety p=.014. Conclusion; The conclusion is that there is a relationship between knowledge, age, parity and level of education with the anxiety of third trimester maternal before delivery. It is recommended for all health workers especially those in the Independent Bunda Abror Practice Midwife to provide IEC about changes during pregnancy and signs of symptoms before delivery, so that mothers do not experience anxiety before the birth process. Keywords: Anxiety, Knowledge, Age, Parity and Education Level